The rights of the child : legal, political and ethical challenges - Adami, Rebecca; Kaldal, Anna; Aspán, Margareta (Stockholm studies in child law and children's rights ;, 2023)
"How can human rights for children born outside their national jurisdiction with parents deemed as terrorists be safeguarded? In what ways do children risk being discriminated in their welfare rights in Sweden when treated as invisible part of a family? How can we do research on children's rights in not just ethically sensitive ways but also with respect for children as rights subjects? And what could be a theory on social justice for children? These are questions discussed in studies from different disciplines concerning children's international human rights, with a special focus on the realization of the CRC in Sweden"--